2012
DOI: 10.1007/s11010-012-1545-y
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of MACC1 expression suppressed hepatocellular carcinoma cell migration and invasion and inhibited expression of MMP2 and MMP9

Abstract: Expression of MACC1 (metastasis-associated in colon cancer-1) protein is associated with metastasis of various human cancers. This study analyzed MACC1 protein expression in hepatocellular carcinoma (HCC) tissue specimens and then investigated the effects of MACC1 knockdown on HCC cell migration and invasion, and gene expression levels. Sixty pairs of HCC and adjacent normal liver tissues from HCC patients were analyzed for MACC1 expression immunohistochemically. The HCC cell lines Hep3B, Huh7, MHCC97H, SMMC-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 27 publications
4
55
0
Order By: Relevance
“…MMPs are proteolytic enzymes, and their basic mechanism of action is to degrade proteins in the ECM. MMPs, particularly MMP-2 and MMP-9 have long been associated with cancer cell metastasis in HCC (5,23). In the present study, the expression levels of MMP-2 and MMP-9 were significantly downregulated in vitro Accumulating evidence has demonstrated that the SHH signaling pathway serves an important role in the development and progression of HCC (8,(24)(25)(26)(27).…”
Section: Discussionsupporting
confidence: 51%
“…MMPs are proteolytic enzymes, and their basic mechanism of action is to degrade proteins in the ECM. MMPs, particularly MMP-2 and MMP-9 have long been associated with cancer cell metastasis in HCC (5,23). In the present study, the expression levels of MMP-2 and MMP-9 were significantly downregulated in vitro Accumulating evidence has demonstrated that the SHH signaling pathway serves an important role in the development and progression of HCC (8,(24)(25)(26)(27).…”
Section: Discussionsupporting
confidence: 51%
“…TPX2 has been demonstrated to be upregulated in salivary gland carcinoma, lung carcinoma and ovarian cancer, with its abnormal expression involved in tumorigenesis and malignant progression (15,16,31). Furthermore, overexpression of TPX2 can suppress the completion of mitosis and disturb the physiological activation of its own channels (32). Matrix metalloproteases (MMPs) are known to degrade the components of the extracellular matrix, and are also particularly important for tumor invasion and metastasis (33).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that extracellular MMP-2 and MMP-9 are overexpressed in various types of cancer (13)(14)(15). As demonstrated in Fig.…”
Section: Mir-524-5p Transfection Attenuates Cell Invasion By Inhibitimentioning
confidence: 94%